Socially Supported by an Embodied Agent: The Development of a Virtual-Reality Paradigm to Study Social Emotion Regulation - Stallmann, Lina; Dukes, Daniel; Tran, Michel; Durand de Gevigney, Valentin; Rudrauf, David; Samson, Andrea C. (Frontiers in Virtual Reality, 2022)
Social emotion regulation, which can be understood as the intentional efforts by one person to regulate emotions of another person, is something we encounter and benefit from every day, and becomes especially important when a person is unable to handle an emotion or an emotional event by themselves. A paradigm that examines whether someone can perceive and benefit from regulatory efforts by another person, represented here by a virtual agent, would be highly relevant for experimental studies investigating social emotion regulation, as well as for interventions in the clinical and sub-clinical context. Virtual reality (VR) provides perhaps the ideal opportunity to test social interactions and difficulties with them, as it counters typical methodological problems of behavioral experiments, such as the trade-off between ecological validity and experimental control, as well as the difficulty of replicating social situations. The goal of the present methods paper is twofold: to provide a detailed description of the development of a novel paradigm consisting of two scenarios in VR designed to test the efficacy of social emotion regulation, and to present the anticipated results for the target populations of typically developing and autistic youth. Participants are presented with a virtual school environment and take part in two activities with a class of students and a teacher, all of whom are virtual agents. In both scenarios, participants experience a potentially stressful situation and are subsequently offered emotional support by a friendly student. Throughout the experiment, self-reports in the form of virtual smiley scales and psychophysiological measurements are collected as markers of the participants’ emotional states. Pilot results will be discussed in line with anticipated outcomes, to indicate that the experiment will be able to show the efficacy of social support by a virtual agent and provide insight into social emotion regulation for different populations. The school environment and the character of the friendly student also have the potential to be adapted for follow-up experiments on additional aspects of social emotion regulation for a variety of contexts.